The voice of the Indian Mona Lisa: Gender and culture in eighteenth-century Rajasthan - Rika Maria Pauwels, Heidi, 1963- (Cambridge, UK; New York, USA: Cambridge University Press, 2023)
"Through literary and art-historical analysis, Pauwels brings to life the vibrant cultural production center of Kishangarh in the eighteenth century. Reconstructing how Bani-thani came to be acclaimed as "India's Mona Lisa," she conveys new insights in the history of Hindi literature, devotion, palace women, and social mobility of the enslaved"--
The Making of the "Indian Mona Lisa" -- The Queen and the Slave Girl -- Becoming the Prince's Concubine -- Synergy of the Literary Couple -- Legacy: Self-Fashioning and its Limits.
Includes bibliographical references and index.
Keywords: Bani Thani, -- active 1750.; Courtesan -- India -- Kishangarh -- Biography; Kishangarh (India) -- Intellectual life -- 18th century; Kishangarh (Princely State) -- Intellectual life -- 18th century; Rajasthan (India) -- Intellectual life -- 18th century